Efektivitas dan Keamanan Furosemid Continuous Infusion Dosis 10 dan 20 mg/jam pada Pasien Penyakit Ginjal Kronik Kondisi Fluid Overload Syndrome disertai Hipoalbumin di RSUD Abdul Wahab Sjahranie - Setiadi, Diga Albrian; Widyati, Widyati; Yakti, Kuntjoro (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2020)
Furosemide continuous infusion is the first choice drug in overcoming the condition of Fluid overload syndrome with hypoalbuminemia in patients with Chronic Kidney Disease (CKD). However, in these conditions, the dose of furosemide used by clinicians is between 10 and 20 mg/hour. No studies have compared the effectiveness and safety of different doses of furosemide. This study aimed to evaluate the effectiveness and safety of 10 and 20 mg/hour furosemide given in continuous infusion in CKD patients with fluid overload syndrome with hypoalbuminemia. The method is a Single-blind, Randomized Clinical Trial conducted during the period of February-April 2017 in the inpatient ward of Abdul Wahab Sjahranie Hospital. Data processing was carried out by statistical analysis, Two Independent T-Test parametric test for data that normally distributed and those that did not correlate with each other, whereas for data that not normally distributed and those that did not correlate with each other, non-parametric test Mann Whitney and Wilcoxon were used. Outcomes studies were 24-hour urine volume, shortness of breath, duration of oxygen consumption, Ronchi and safety of therapy seen from drug side effects (hypotension, hyperuricemia, hyperglycemia, hyponatremia, hypokalemia). The results of the study, 34 patients with CKD with fluid overload syndrome with hypoalbuminemia (2.5-3.0 g/dL) were registered. On the effectiveness of therapy, there was no significant difference in 24-hour urine volume (P = 0.324; P> 0.05; 95%; CI=714.6-1017.8 ml group 1; CI=818.0-1113.2 ml group 2), shortness of breath (P = 0.781; P> 0.05; 95 % CI=0.68-1.32 group 1; CI=0.72-1.40 group 2), duration of oxygen use (P = 0.363; P> 0.05; 95% CI=1.34-2.66 day group 1; CI=1.72-3.10 day group 2), Ronk (P = 0.692; P> 0.05 ) and the absence of drug adverse events (P = 1.000; P> 0.05) between the two groups. In conclusion, the dose of 10 and 20 mg/hour furosemide has the same